Exploring the Efficacy of Essential Oils in Laboratory Conditions for Controlling Mediterranean Fruit Fly Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) - Özdemir, Esengül (My University, 2023)
The Mediterranean fruit fly (Medfly), Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), poses a significant threat to agriculture worldwide. This study examines the potential insecticidal effects of essential oils from Mentha arvensis and Cinnamomum zeylanicum on controlling C. capitata under laboratory conditions. Even at low concentrations, toxicity assays indicated that both essential oils significantly increased the mortality of adult Medflies. The concentration-dependent effect of these oils on C. capitata mortality is demonstrated, with Mentha arvensis achieving 100% mortality within 48 hours at 1% concentration and Cinnamomum zeylanicum exhibiting rapid efficacy, reaching a low LC50 value after only 1 hour of application. The concentration and application time of essential oils were found to have a significant impact on their effectivness. This study highlights the potential of essential oils for controlling C. capitata populations. Essential oils offer a sustainable and eco-friendly alternative for managing C. capitata but further studies are necessary for their successful incorporation into integrated pest management programs.
Keywords: Mentha arvensis; Cinnamomum zeylanicum; Biopesticides; Essential Oil; Insecticidal properties